The Misconception of Defining Sufi Thought As Pantheism - Allahverdiyev, İbrahim (Scholarya Demo Journal of Ruby, 2021)
Islamic mysticism and the theological ideas of Sufis, especially the understanding of vahdet-i vujud (unity of being), are often described as pantheism by different researchers. However, the mystical thinkers who define themselves as the western interpretation of Islam based on the Qur’an and hadiths, certainly do not have such an assessment. Pantheism thought is a philosophical trend and naturally is based on only rational evidence. Although similar expressions are used by the representatives of both groups from time to time, one differs from the other in terms of theoretical or operational aspects. In Sufi theory, mysticism does not only reveal rational proofs, on the contrary, he claims that the proofs of the mind are obtained through spiritual inspiration. He also states that the source of spiritual inspiration is worship and contemplation. Therefore, it is a great mistake to identify Islam with pantheism, which is in contradiction with thought, for people who devote almost all of their lives to spiritual devotion and spend their lives with prayers. In the article, we referred to the thoughts of Muhyiddin ibn Arabi, who represented the idea of the unity of being and influenced the overwhelming majority of Islamic mystics with his thoughts, and who was accepted as Shayhu’l-Akbar by his Sufism wise men. The idea of unity of being and its examples were briefly discussed. It was emphasized that these ideas are in contradiction with the pantheist theory, which follows the proposal "The world is God, or God is the world" and limits God only to the realm. That is to say, while there is an identity with God in pantheism, that is, God does not have a separate and independent existence from the universe, the realm in the unity of the body is the manifestation of God’s names and attributes, so God has an existence independent of the realm in person.